2011
DOI: 10.1016/j.clinph.2010.05.023
|View full text |Cite
|
Sign up to set email alerts
|

N170 asymmetry as an index of inferior occipital dysfunction in patients with symptomatic occipital lobe epilepsy

Abstract: a b s t r a c tObjective: Localizing epileptic foci in posterior brain epilepsy remains a difficult exercise in surgery for epilepsy evaluation. Neither clinical manifestations, neurological, EEG nor neuropsychological evaluations provide strong information about the area of onset, and fast spread of paroxysms often produces mixed features of occipital, temporal and parietal symptoms. We investigated the usefulness of the N170 event-related potential to map epileptic activity in these patients. Methods: A grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
3
5
0
Order By: Relevance
“…The normal results of the N170 visual-evoked potentials support normal lower occipital lobe function in the neighborhood of the fusiform gyrus [12], a result consistent with the normal function of the ventral visual pathway. This is in line with previous studies which have demonstrated a normal level of performance of these patients in a wide range of neuropsychological tests, namely, those evaluating occipital lobe function [9,20].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…The normal results of the N170 visual-evoked potentials support normal lower occipital lobe function in the neighborhood of the fusiform gyrus [12], a result consistent with the normal function of the ventral visual pathway. This is in line with previous studies which have demonstrated a normal level of performance of these patients in a wide range of neuropsychological tests, namely, those evaluating occipital lobe function [9,20].…”
Section: Discussionsupporting
confidence: 72%
“…The N170 right to left hemisphere ratio was within the normal range defined in Lopes et al [12] in all cases except in patient 1 where it was increased (1.82). The average N170 ratios for the patients with left hemisphere spikes (1.00), right spikes (0.96), or independent bilateral spikes (0.98) were also within the normal range and overlapping.…”
Section: Clinical and Neurophysiological Evaluationsupporting
confidence: 72%
See 2 more Smart Citations
“…However, it has been linked to both clinical and non-clinical anxieties, which support a role in TAF: Alterations in the upper beta frequencies have been found in comparisons between non-clinical controls and OCD patients (Maihöfner et al, 2007; Velikova et al, 2010) and schizophrenic patients (Yeragani et al, 2006). Furthermore, synchronized activity in the upper beta band has been found during modulations of a sense of agency (Kang et al, 2011). …”
Section: Discussionmentioning
confidence: 99%